Bendix Model 1111 Time-of-Flight Mass Spectrometer - Bendix Corporation (1970)
General view of a Bendix Model 1111 Time-of-Flight Mass Spectrometer, with view of the ion source and assorted control panels. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Ion sources; Mass spectrometers